Optimalisasi Tumbang Melalui Hidup Bersih Dan Sehat Pada Anak - ferasinta; Ferasinta Ferasinta; Selvia Novitasari; Panzilion Panzilion (JURNAL PENGABDIAN KESEHATAN, 2022)
Hands are the parts of our body that are most contaminated with dirt and germs. When holding something, and shaking hands, of course there are germs that stick to the skin of our hands. After holding the door to the restroom (the source of disease that comes from human feces), holding money, through the handles of public transportation seats, public telephone handles, and parts in public places, hands are almost certainly contaminated with germs of any kind. The habit of washing hands properly is not only influenced by how to wash them. How to wash with the right steps can eliminate germs on your hands.